A strategy for breaking the MOF template to obtain small-sized and highly dispersive polyoxometalate clusters loaded on solid films1. Issue 28 (28th July 2015) - Li, Jian-Sheng; Sang, Xiao-Jing; Chen, Wei-Lin; Zhang, Lan-Cui; Zhu, Zai-Ming; Li, Yang-Guang; Su, Zhong-Min; Wang, En-Bo
<x xml:space="preserve">Abstract</x> Highly dispersed and small sized POM nanoclusters that were fabricated using MOF materials can result in a significant performance enhancement of QDSCs.